Clinical Heterogeneity in Cerebral Hemiatrophy Syndromes. Issue 1 (18th January 2016) - Reiter, Eva; Heim, Beatrice; Scherfler, Christoph; Mueller, Christoph; Nocker, Michael; Ndayisaba, Jean‐Pierre; Loescher, Wolfgang; Seppi, Klaus; Lees, Andrew J.; Warner, Thomas; Poewe, Werner; Wenning, Gregor K.; et al.
Abstract: Background: Cerebral hemiatrophy syndromes can present with variable neurological symptoms. In childhood epilepsy, mental retardation and neuropsychiatric disorders are common while in adults movement disorders, such as highly asymmetric parkinsonism or hemidystonia as well as neuropsychiatric problems have been reported. Methods: Here, we present three adult patients with features that expand the clinical spectrum and give an overview of the most common clinical signs associated with this rare condition. Results: All three patients had prominent neuropsychiatric symptoms such as mood swings and increased irritability. Furthermore, one patient developed hemichorea which can be a rare presentation of cerebral hemiatrophy. Conclusions: Cerebral hemiatrophy syndromes are a heterogeneous group of disorders that may also present with neuropsychiatric symptoms or hemichorea.